A lemon myrtle extract inhibits glucosyltransferases activity of Streptococcus mutans. Issue 9 (2nd September 2018) - Yabuta, Yukinori; Mukoyama, Haruka; Kaneda, Yoshimi; Kimura, Narisa; Bito, Tomohiro; Ichiyanagi, Tsuyoshi; Ishihara, Atsushi; Watanabe, Fumio
ABSTRACT: Streptococcus mutans is a bacterium found in human oral biofilms (dental plaques) that is associated with the development of dental caries. Glucosyltransferases (GTFs) are key enzymes involved in dental plaque formation, and compounds that inhibit their activities may prevent dental caries. We developed a screening system for GTF-inhibitory activities, and used it to profile 44 types of herbal tea extracts. Lemon myrtle ( Backhousia citriodora ) extract exhibited the highest GTF-inhibitory activity, with an IC50 for GTF in solution of 0.14 mg mL −1 . Furthermore, lemon myrtle extracts had the third-highest polyphenol content of all tested extracts, and strongly inhibited S. mutans biofilm. Interestingly, lemon myrtle extracts did not inhibit cell growth. Graphical abstract: : Glucosyltransferases-inhibitory activities of 44 types of herbal tea extracts.